Analysis of erythroid maturation in the nonlysed bone marrow with help of radar plots facilitates detection of flow cytometric aberrations in myelodysplastic syndromes. Issue 5 (16th June 2020) - Violidaki, Despoina; Axler, Olof; Jafari, Katayoon; Bild, Filippa; Nilsson, Lars; Mazur, Joanna; Ehinger, Mats; Porwit, Anna
Abstract: Background: Accumulating data support the role of flow cytometry (FCM) in diagnostic work‐up of myelodysplastic syndromes (MDS). Changes in erythropoiesis are less documented than in granulopoiesis. However, most studies were performed on bone marrow samples (BMSs) after red blood cell lysis. We have established a FCM protocol for erythropoiesis, following a no‐lysis approach and live gate acquisition of nucleated cells using DNA dye DRAQ5. Methods: The ERY tube consisted of CD36, CD71, CD105, CD117, CD13, and CD45. Comparison with cytomorphological differential counts was carried out in a learning cohort of 80 BMS. To detect aberrations, we analyzed 208 BMS from 135 patients and five normal donors, divided into three cohorts: MDS ( n = 68), nonclonal cytopenia ( n = 43), and normal controls ( n = 29). Radar plot (RP) was created for an overview of normal and aberrant patterns. Results: The proportion of erythropoiesis in the ERY tube showed better agreement with the cytomorphology, compared to FCM panels on lysed BMS. We confirmed that aberrations in coefficient of variation (CV) of CD36 fluorescence intensity ( p  < .001), mean fluorescence intensity of CD36 ( p = .012), and CV of CD105 ( p  < .001) can distinguish between MDS and nonclonal cytopenia. RP facilitated evaluation of erythropoietic maturation patterns and aberrant patterns were identified in 85% of MDS patients. Conclusion: This study provides evidence that a no‐lysis approach and RP analysis allow a more reliable evaluation of erythropoiesis and erythroid dysplasia, supporting the integration of FCM erythroid panels in the standard work‐up of MDS.